2018
DOI: 10.32693/bomg.32.2.2017.377
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of PAHs (Polycyclicaromatic Hydrocarbons) Pollutant in Sediment of The Banten Bay

Abstract: Banten Bay is end of stream for a few rivers from Banten mainland where many manufactures and petrochemical industries are built. This may give environmental pressure of water quality of the bay due to pollutant input, such as Polycyclic Aromatic Hydrocarbons (PAHs). This study is to identify those pollutants and determine their total concentration and distribution in sediments. Surface sediment samples were collected in four zones: inner coastline within the bay, middle bay, coastline off the bay and outer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Penentuan konsentrasi PAH secara kuantitatif menunjukkan bahwa konsentrasi total PAH (TPAH) tertinggi terdeteksi di stasiun TJU 1 Muara Tanjung Uban yaitu sebesar 13,492 ng.g -1 berat basah. Hal ini dimungkinkan terjadi karena menurut Baek (27) dan Khozanah (28) , lokasi dekat muara sungai umumnya merupakan tempat terakumulasinya polutan PAH. Lokasi stasiun TJU 1 ini merupakan lokasi yang dekat dengan muara sungai dan tempat terjadinya proses akumulasi sedimen baik yang berasal dari daratan yang dibawa oleh arus sungai maupun yang berasal dari muara laut.…”
Section: Konsentrasi Dan Distribusi Pahunclassified
“…Penentuan konsentrasi PAH secara kuantitatif menunjukkan bahwa konsentrasi total PAH (TPAH) tertinggi terdeteksi di stasiun TJU 1 Muara Tanjung Uban yaitu sebesar 13,492 ng.g -1 berat basah. Hal ini dimungkinkan terjadi karena menurut Baek (27) dan Khozanah (28) , lokasi dekat muara sungai umumnya merupakan tempat terakumulasinya polutan PAH. Lokasi stasiun TJU 1 ini merupakan lokasi yang dekat dengan muara sungai dan tempat terjadinya proses akumulasi sedimen baik yang berasal dari daratan yang dibawa oleh arus sungai maupun yang berasal dari muara laut.…”
Section: Konsentrasi Dan Distribusi Pahunclassified
“…Several bacteria were isolated from marine biota, especially marine sponge microsymbionts, for example, Bacillus sp. strain AB353f, B. pumilus strain GLB197, B. cohnii strain DSM 6307, and Acinetobacter Calcoaceticus strain PHCDB14 [9,[63][64][65]. Microorganisms associated with mangroves have also been identified to carry out the biodegradation function of PAHs [40,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, based on the geographical condition, Banten Bay is full of maritime activities acting as the shipping route to bridge 2 big islands, Java and Sumatera [6]. Moreover, a massive development from oil and gas refinery, industries, and manufacturers, enhances the industrial activities in the neighboring site which may potentially impact the marine environment and water quality [7]. Related to the natural processes, the hydrodynamic in Banten Bay is mostly influenced by ocean-atmosphere interactions in the Java Sea in which the previous study has been suggested that the dynamic of hydrodynamic processes in Banten relating to the monsoonal season will potentially induce the accretion and abrasion along the Banten Bay coastal region [8].…”
Section: Introductionmentioning
confidence: 99%